Distribution patterns of cardiovascular disease risk factors among youth in turkestan region of the republic of kazakhstan by gender, age, education level and social status (Bangladesh Journal of Medical Science, 2026)
Background Cardiovascular diseases (CVD) remain the leading cause of mortality worldwide and in Kazakhstan. Understanding the distribution of risk factors among youth is crucial for developing targeted prevention strategies. Objective To analyze the prevalence of cardiovascular disease risk factors among youth aged 14-34 years in Turkestan region of Kazakhstan, stratified by gender, age, education level, and social status. Materials and methods A cross-sectional study was conducted with 1,496 respondents (males: 647, 43.2%; females: 849, 56.8%) from 21 healthcare facilities in Turkestan region. Structured questionnaires assessed sociodemographic characteristics, health status, chronic diseases, and health awareness. Statistical analysis included descriptive statistics, chi-square tests, and 95% confidence intervals. Results Overall prevalence of chronic diseases was 32.3% (95% CI: 29.9-34.8%). Obesity was identified in 8.6% (95% CI: 7.2- 10.2%), arterial hypertension in 2.9% (95% CI: 2.1-4.0%), and thyroid disorders in 3.7% (95% CI: 2.7-4.9%). Significant gender differences were observed: males had higher rates of arterial hypertension (3.4% vs 2.6%, p=0.041), while females showed higher prevalence of thyroid disorders (5.2% vs 1.7%, p